La società in bicicletta: storia di un’avventura culturale lungo due secoli: Pivato, S. (2019). Storia sociale della bicicletta. Bologna: Il Mulino. - Tirino, Mario (Eracle. Journal of Sport and Social Sciences, 2021)
The paper examines the sociocultural transformations of cycling from the late nineteenth century to the 2000s. Retracing some stages of the analysis carried out by historian Stefano Pivato in his volume Storia sociale della bicicletta (2019), this paper aims to show how the analysis of cycling practices allows to monitor, describe and analyze the evolution of the political world, cultural values, social identities, daily practices, and lifestyles. From a symbol of modernization, to an icon of “slow” cultures, in over a century the bicycle constitutes a symbolic object still capable of activating memories and social discourses.